The leaving season : a memoir in essays - McMasters, Kelly (W. W. Norton & Company, Inc., 2023)
"Kelly McMasters found herself in her midthirties living her fantasy: she'd moved with her husband, a painter, from New York City to rural Pennsylvania, where their children roamed idyllic acres in rainboots and diapers. The pastoral landscape and the bookshop they opened were restorative at first, for her and her marriage. But soon, she was quietly plotting her escape. In The Leaving Season, McMasters chronicles the heady rush of falling in love and carving out a life in the city, the slow dissolution of her relationship in an isolated farmhouse, and the complexities of making a new home for herself and her children as a single parent. She delves into the tricky and often devastating balance between seeing and being seen; loss and longing; desire and doubt; and the paradox of leaving what you love in order to survive. Whether considering masculinity in the countryside through the life of a freemartin calf, the vulnerability of new motherhood in the wake of a car crash, or the power of community pulsing through an independent bookshop, The Leaving Season finds in every ending a new beginning."--Amazon.